2012
DOI: 10.1097/mlr.0b013e318270bad4
|View full text |Cite
|
Sign up to set email alerts
|

Disparities in Potentially Avoidable Emergency Department (ED) Care

Abstract: Disproportionately higher use of EDs for ACSC care exists for many priority populations and across a broader range of priority populations than previously documented. These differences constitute disparities in potentially avoidable ED visits for ACSC. To avoid exacerbating disparities, health policy efforts to minimize economic inefficiencies in health care delivery by limiting ED visits for ACSC should first address their determinants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
110
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(120 citation statements)
references
References 40 publications
8
110
1
1
Order By: Relevance
“…Gallagher et al 16 concluded homeless individuals with non-Medicaid insurance were the most likely to have a usual source of care; suggesting that those with Medicaid insurance had difficulty obtaining a usual source of care. Similarly, Johnson et al 34 found that the probability for being admitted to the ED for an ACS condition was highest among publicly insured patients in the general population. These findings further support that insurance alone does not increase access to health services, especially to primary care services.…”
Section: Improving Health Policy Initiativesmentioning
confidence: 99%
See 2 more Smart Citations
“…Gallagher et al 16 concluded homeless individuals with non-Medicaid insurance were the most likely to have a usual source of care; suggesting that those with Medicaid insurance had difficulty obtaining a usual source of care. Similarly, Johnson et al 34 found that the probability for being admitted to the ED for an ACS condition was highest among publicly insured patients in the general population. These findings further support that insurance alone does not increase access to health services, especially to primary care services.…”
Section: Improving Health Policy Initiativesmentioning
confidence: 99%
“…16 On the contrary, previous research found women have a higher probability for being admitted for an ACS condition, indicating that housed women have more barriers to primary care services than housed men. 34,44 This disparity suggests homeless women may have access to additional resources that are unavailable to nonhomeless women. The majority of homeless families are headed by women, which may indirectly increase the number of available health-related resources.…”
Section: Identifying At-risk Subpopulationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Patient factors which are associated with increased ED utilization for non-urgent care include inadequate health literacy (11), advanced age, female gender, poverty and minority race (12). After discharge from the ED, patients face substantial barriers in obtaining appropriate follow-up care.…”
Section: With Challenge Comes Opportunitymentioning
confidence: 99%
“…[7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] Overall we found four common approaches used to define preventable ED visits: 1) Ambulatory Care Sensitive Conditions (ACSCs) (N = 7), 2) Low Acuity/ low intensity visits (N = 5), 3) New York University (NYU) (Billings) Algorithm (N = 3) and 4) hospital admission vs. non-admission (N = 1). Overall the proportion of preventable ED visits identified by these studies ranged from 5.7% to 74.2%.…”
Section: Literature Searchmentioning
confidence: 99%